Distribution of additional virulence factors related to adhesion and toxicity in Shiga toxin-producing Escherichia coli isolated from raw products in Argentina - Cadona, Jimena Soledad (2013)
A total of 73 Shiga toxin-producing Escherichia coli (STEC) isolates, belonging to 25 serotypes and isolated from raw products in Argentina, were examined for the occurrence of genes responsible for bacterial adhesions to intestine, ehaA (EHEC autotransporter), lpfAO113 (long polar fimbriae), sab (STEC autotransporter [AT] contributing to biofilm formation), ecpA (E. coli common pilus), hcpA (haemorrhagic coli pilus), elfA (E. coli laminin-binding fimbriae), sfpA (sorbitol-fermenting EHEC O157 fimbriae plasmid-encoded) and of the toxigenic gene cdt-V (cytolethal distending toxin). Our study showed different adhesin profiles that are not linked to one specific serotype and that all analysed isolates possess, besides stx genes, some adherence genes. Several of the isolates contained also multiple toxin genes. The results of the present work alert the presence of genes coding for additional adhesins and cdt-V toxin in LEE-negative STEC strains that occur in foods, and this traits could increase their pathogenic potential.